1983
DOI: 10.1118/1.595391
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography with a linear accelerator with radiotherapy applications

Abstract: An earlier paper [Simpson et al., Med. Phys. 9, 574 (1982)] described a computed tomography (CT) scanner that was constructed by adding a detector array to a 4-MV isocentric linear accelerator. Since the previous article, the detector array has been improved and we now demonstrate better than 3-mm spatial resolution and better than 1% relative electron density discrimination. A series of pictures from volunteer patients is included. Normal anatomy is visualized with bone, muscle, fat, and air being clearly del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(34 citation statements)
references
References 0 publications
1
33
0
Order By: Relevance
“…The third generation megavoltage CT system previously reported by the authors [20] has been shown to produce better quality images than those reported by Swindell et al [21]. The current image quality of these third generation designs remains much worse than that attained in conventional diagnostic CT scanners.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The third generation megavoltage CT system previously reported by the authors [20] has been shown to produce better quality images than those reported by Swindell et al [21]. The current image quality of these third generation designs remains much worse than that attained in conventional diagnostic CT scanners.…”
Section: Discussionmentioning
confidence: 93%
“…Such methods are, however, limited to two-dimensional projections for the three-dimensional treatment volume. We have developed and reported a new computed tomographic (CT) scanning technique (megavoltage CT scanning) using a megavoltage X-ray beam emerging from a linear accelerator and have already begun to use it clinically for verification in two ways [19][20][21]. In one way, megavoltage CT scanning is performed after the patient is set on the treatment table.…”
Section: Introductionmentioning
confidence: 99%
“…These high‐Z image artifacts are greatly reduced in MV X‐ray imaging. Past efforts of using the therapeutic MV beams for imaging have proven its feasibility especially in the area of portal imaging while the implementation of megavoltage cone‐beam imaging (MVCB) has also been studied by several different groups 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 and is commercially available (MVision, Siemens Medical Solutions USA, Malvern, PA).…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Another CT imaging technique that is also under investigation for soft tissue visualization involves the use of the megavoltage (MV) therapy beam and an electronic portal imaging device (EPID). [5][6][7][8]11,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Although the intrinsic contrast of human anatomical structures is lower at MV energies compared to kV energies, it has been demonstrated that soft tissues can be visualized on MV CBCT images obtained using conventional, as well as investigational, imagers. 8,24,30,33 In addition, MV CBCT can offer some advantages over the kV technique.…”
Section: Introductionmentioning
confidence: 99%